Technique analysis with the "Weightlifting Analyzer 3.0" - Jentsch, H.; Lippmann, J. (World Congress of Performance Analysis of Sport VIII, 2008)
Based on modern video and computer technology the analysing procedure can contribute to improve a simple two-dimensional and quick analysis of lifting technique in training and competition. The system is easy to handle by coaches. It only requires some basic knowledge in the application of computer and video technology. An initial introduction and training with the software is required and is supported by the programme as the sequential steps for the analyses are presented in a way that anybody can understand and follow. In Germany many coaches and clubs have been working with the system for several years.